2014
DOI: 10.1037/neu0000056
|View full text |Cite
|
Sign up to set email alerts
|

Reading skill in adult survivors of childhood brain tumor: A theory-based neurocognitive model.

Abstract: Objective: This study investigated the relationship between word reading and white matter (WM) integrity within a neuroanatomical-based reading system comparing adult survivors of childhood brain tumors and controls. It was predicted that the association between WM integrity and word reading would be mediated by processing speed, and this indirect effect would be moderated by group. Method: Thirty-seven adult survivors of childhood brain tumor and typically developing adults participated (age M = 24.19 ± 4.51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Along with findings within the CHD literature, research across a wide range of other clinical populations has suggested relationships between lower WMI in specific brain regions and poorer functioning on cognitive measures (Ellmore, Li, Xue, Wong, & Frye, 2013; Genova, DeLuca, Chiaravalloti, & Wylie, 2013; Nestor et al, 2004; Smith, King, Jayakar, & Morris, 2014). Given these findings, it is possible that reduced microstructural connectivity resulting from early disruption could be related to cognitive performance in emerging adults with CHD.…”
Section: Study Two: Relationships Between White Matter Differences Anmentioning
confidence: 91%
“…Along with findings within the CHD literature, research across a wide range of other clinical populations has suggested relationships between lower WMI in specific brain regions and poorer functioning on cognitive measures (Ellmore, Li, Xue, Wong, & Frye, 2013; Genova, DeLuca, Chiaravalloti, & Wylie, 2013; Nestor et al, 2004; Smith, King, Jayakar, & Morris, 2014). Given these findings, it is possible that reduced microstructural connectivity resulting from early disruption could be related to cognitive performance in emerging adults with CHD.…”
Section: Study Two: Relationships Between White Matter Differences Anmentioning
confidence: 91%
“…The 4-subtest Wechsler Abbreviated Scale of Intelligence (WASI; Wechsler, 1999) was administered to obtain estimates of intellectual abilities. WASI has been employed in many research studies of child and adult neurological populations including adults survivors of childhood brain tumor [ 12 , 19 ]. Verbal IQ (VIQ) was based on Vocabulary and Similarities subtests.…”
Section: Methodsmentioning
confidence: 99%
“…Rarely do studies examine brain tumor survivors treated with radiation versus no radiation treatment [ 8 ] and relative to non-clinic referred healthy controls. The reports on cognitive correlations with FA are also limited [ 11 , 12 ]. Furthermore, existing studies on the relationship between FA and intellectual performance (IQ) are inconsistent in pediatric brain tumor patients [ 6 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies in survivors of pediatric brain tumor have found reduced white matter integrity in specific tracts ( Aukema et al, 2009 ; King et al, 2015b ; Mabbott et al, 2006 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2010 ; Smith et al, 2014 ) and that the integrity of these tracts is associated with performance on neurocognitive measures of processing speed, motor speed, full scale IQ, fine motor function, working memory, memory, and executive functioning ( Aukema et al, 2009 ; Brinkman et al, 2012 ; Law et al, 2011 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2015 ). These studies suggest that structural changes to white matter may represent the neurobiological underpinnings of outcomes.…”
Section: Introductionmentioning
confidence: 99%